Manufacturing Process And Tonase Calculation On Bumper Rear Axle Bracket Rh - Febrian Aliandi; Abdul Muchlis; Sandy Suryady (Publisher Cv. Inara, 2021)
Rear Axle Bumper Bracket is a non-frame part of the car that functions to connect the bumper itself to the rear axle and to withstand collisions and also reduce collisions. Rear Axle Bumper Brackets are commonly used for vehicle components. This writing aims to determine the process of making the Rear Axle RH Bumper Bracket and the total force in the blanking (cutting) process and also in the bending (bending) process of the RH Rear Axle Bumper Bracket Lower Part. Bumper Rear Axle Bracket RH is made by going through a material formation process by cutting blanking and bending, followed by a welding process using spot welding to the painting stage using a powder coating method of dipping. Based on the results of calculations using SPH 440 OD material for the main material for making Bracket Bumper Rear Axle RH Lower Part, it was found that the amount of tonnage that occurred in the blanking process (cutting) was 84.09 Tons with an added reserve force of 8.41 Tons with a value of 84.09 Tons. safety factor of 1.3 which has been standardized on the use of static loads so as to produce the capacity of the press machine needed for the blanking process (cutting) which is 120.25 tons with the actual press machine used of 110 tons. For the bending process, it can be done with a total bending force of 27.19 tons with the added pad force in the bending process of 6.8 tons so that the total force on the Press machine needed for the bending process is 34 tons with the actual press machine. used is 110 tons.